1995
DOI: 10.1128/jvi.69.8.4607-4618.1995
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovirulent phenotype of coxsackievirus B3 is determined at a single site in the genomic 5' nontranslated region

Abstract: We report the construction of chimeric coxsackievirus B3 (CVB3) strains in which sequences of an infectious cDNA copy of a noncardiovirulent CVB3 genome were replaced by the homologous sequences from a cardiovirulent CVB3 genome to identify which of 10 predicted genetic sites determine cardiovirulence. Cardiovirulent phenotype expression was consistently linked to nucleotide 234 (U in cardiovirulent CVB3 and C in avirulent CVB3) in the 5 nontranslated region. Reconstructions of the parental noncardiovirulent C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(57 citation statements)
references
References 88 publications
1
54
1
1
Order By: Relevance
“…These data demonstrate that, in a host deficient in GPX-1 activity, an avirulent virus undergoes a phenotypic change to virulence due to point mutations in the genome. Single mutations in various sites in the CVB3 genome have been shown to be associated with cardiovirulence (26,27). Our previous work demonstrating similar point mutations in Se-defi-cient mice suggests that the mutations may be driven by oxidative damage.…”
Section: Discussionmentioning
confidence: 93%
“…These data demonstrate that, in a host deficient in GPX-1 activity, an avirulent virus undergoes a phenotypic change to virulence due to point mutations in the genome. Single mutations in various sites in the CVB3 genome have been shown to be associated with cardiovirulence (26,27). Our previous work demonstrating similar point mutations in Se-defi-cient mice suggests that the mutations may be driven by oxidative damage.…”
Section: Discussionmentioning
confidence: 93%
“…Sequencing of the viral genomic RNA obtained from infected Se-adequate and Se-deficient mice confirmed that a viral genome change had occurred ( Table 1). Out of the ten nucleotide positions that were reported to co-vary with cardiovirulence in CVB3 strains [12], six reverted to the virulent genotype in those virions that replicated in Se-deficient mice [1]. No nucleotide changes were found in viral genomes isolated from Se-adequate control mice.…”
Section: Coxsackievirus and Keshan Disease: The Nutrition-virus Nexusmentioning
confidence: 93%
“…An amino acid substitution in encephalomyocarditis virus (EMCV) can render the virus diabetogenic (42). Cardiovirulence of coxsackievirus B3 can be determined by a single site at the 5= untranslated region (UTR) (815). (For additional studies on coxsackievirus B pathogenesis and evolution and the relevance of quasispecies for enteroviruses in general, see several chapters of references 232 and 812).…”
Section: Cell Tropism and Host Range Mutants: Biological Alterations mentioning
confidence: 99%